Penerapan Peralatan Georadar Sebagai Teknologi Pendukung Pemantauan Perilaku Bendungan Studi Kasus: Bendungan Cacaban, Jawa Tengah - Nurlia Sadikin (JURNAL SUMBER DAYA AIR, 2011)
Dam is a quite complex and highly risky building in the case of failure or damage, therefore continuously monitoring should be carried out in order to monitor the behavior of the dam. The development of science and technology has provided supporting methods of investigating the performance of hydraulic structures. The existence of cavities which can lead to seeps and detection of damages by seepage on earlier phases in dams could be detected by georadar. On August 2010, implementation of georadar application was conducted into Cacaban Dam, Central Java. There were suspections of seepage in the lower side of the dam body. Measurement lines used for georadar were 6 lines along the dam body and 4 lines across the spillway. The results showed that in the dam body the soil was divided into 2 layers, the top layer showing color variation while the lower layer was homogeneous. On the spillway, results of georadar investigation also showed that the soil was divided into 3 layers. The top and middle layers show color variations, which the middle layer was more contrast and varied and the bottom layer was homogeneous. Deviations showed between the theoretical phreatic lines with phreatic line of piezometers and measured by georadar. These deviations occurred due to the reflector amplitude value and variation of density levels inside theembankment.